Impairment of Mitochondrial Biogenesis and Dynamics Involved in Isoniazid-Induced Apoptosis of HepG2 Cells Was Alleviated by p38 MAPK Pathway - Zhang, Tianguang; Ikejima, Takashi; Li, Lizhong; Wu, Ruiqin; Yuan, Xiaoyan; Zhao, Jun; Wang, Yimei; Peng, Shuangqing (Frontiers in Pharmacology, 2017)
Isoniazid (INH), a widely used first-line antitubercular drug, has been noted to be associated with hepatotoxicity. In spite of extensive researches over many decades, the mechanism of INH-induced hepatotoxicity still remains poorly understood. Recently, mitochondrial toxicity has been emerging as a new paradigm for INH-induced hepatotoxicity. In this study, we showed that INH impaired mitochondrial biogenesis and dynamics in human hepatocarcinoma HepG2 cells. INH reduced mitochondrial membrane potential (MMP) and induced mitochondria swelling. INH also inhibited the protein expressions of three major mitochondrial biogenesis regulators, SIRT1, PGC1α and NRF1, along with increased acetylation of PGC1α. Meanwhile, INH decreased the number of mitochondria, accompanied by decreased expression of mitochondrial protein COX IV. INH caused mitochondrial fragmentation involving decreased levels of the fusion protein MFN2 as well as the fission protein DRP1. INH-reduced DRP1 expression was associated with the increase of apoptosis, suggesting the existence of pro-survival fission and its involvement in mitochondrial quality control. INH activated p38 MAPK, whereas inhibition of p38 MAPK aggravated INH-induced decreases of SIRT1, PGC1α, NRF1, COX IV and DRP1 expressions. P38 MAPK inhibition also further up-regulated the acetylation of PGC1α and exacerbated INH-induced MMP loss, mitochondrial swelling and apoptosis. Taken together, INH-activated p38 MAPK induced mitochondrial biogenesis to alleviate apoptosis through partly recovering SIRT1-PGC1α pathway activation. In the meantime, p38 MAPK activation by INH promoted protective mitochondrial fission to alleviate apoptosis by partial recovery of DRP1 expression.